In the presence of Hearing, Senses to Listen - Rafaela Aline Wenzel; Sandra Regina Simonis Richter (Universidade de Santa Cruz do Sul – UNISC, Santa Cruz do Sul/RS, Brazil) (Revista Brasileira de Estudos da Presença, 2019)
ABSTRACT – In the Presence of Hearing, Senses to Listen – This essay brings together phenomenological studies on the language’s poetical dimension to address the actions of hearing and listening as distinct aspects in the experience of producing senses. The paper establishes an interlocution between philosophy and poetics to think about the inseparability between body and world, rhythm and voice, highlighting the educational relevance of the aesthesic experience of listening to the world as a founding resonance of senses that are organized, situated and expressed in language.